TESTING OF VENTURI-TYPE INJECTOR PERFORMANCE FOR FISH AQUACULTURE SYSTEM - Nova Amanta, Diar
Oxygen is one of the important aspects in the determination of water quality of fish aquaculture system. Problem which often occured in fish aquaculture water is the increasing of ammonia level. Ammonia can be decomposed by the role of decomposing bacteria contained in biofloc system and dissolved oxygen supply produced from aeration process, hence the dissolved oxygen level will be abundant. In this bachelor thesis research, aeration process was conducted by venturi-type injector and by purpose to determine the effects of water and air flow rate variations toward dissolved oxygen level as well as to compare dissolved oxygen level produced from venturi-type injector with air diffuser-type aerator. This research was conducted by giving variations of water flow rate and air flow rate entering into venturi-type injector. Variations of air flow rate were set to 0, 2, and 4 lpm while variations of water flow rate were set to 6.54, 8.12, and 10.86 lpm. The increasing speed of dissolved oxygen level for each condition was measured using DO meter. The observation for the resulting bubble from venturi-type injector was conducted with DSLR camera. The image result then processed and analyzed with ImageJ image-processing software to determine the average diameter of resulting bubble from venturi-type injector. Results obtained from this research were the highest increasing speed of dissolved oxygen level occur at water flow rate and air flow rate of 10.86 lpm and 4 lpm, respectively. Processed image result showed that the higher water and air flow rate will be followed by higher bubble amount. It can be concluded that the increasing speed of dissolved oxygen level tend to increase when water and air flow rate both increased.